Development of a basic physics practical guide with PhET interactive simulation on the topic of kinematics and dynamics - Puspitasari, Wahyu Dwi; Febrinita, Filda; Andrea, Tarra Hyuga (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2025)
Due to the lack of practical tools for supporting Basic Physics lecture activities, lecturers have turned to PhET Interactive Simulations. However, there is currently no guide to help lecturers and students conduct practical activities using these simulations. This research aimed to develop a guidebook for Basic Physics practicum activities utilizing PhET, evaluated by experts and small-scale users for feasibility. The research followed Borg and Gall’s R&D model, consisting of: (1) data collection, (2) planning, (3) product development, (4) product validation, (5) product revision, and (6) product trials. Data were gathered through observation, interviews, and questionnaires. Product validation was carried out by three experts—one each in material, media, and language. A small-scale product trial involved five randomly-selected students from the 2024/2025 Academic Year. Validation and trial data were analyzed by comparing scores to the maximum possible per question. The resulting product was a basic physics practicum guide using PhET for kinematics and dynamics. Expert validation indicated: (1) very worthy (3.88) by the material expert; (2) worthy (3.12) by the media expert; and (3) very worthy (3.80) by the language expert. The small-scale trial produced an average feasibility score of 3.33. Further research should include large-scale trials of the guide.